STYLES OF IRON ORE MINERALIZATION AT THE SCHWANER MOUNTAINS AREA, SOUTHWEST KALIMANTAN, INDONESIA - , KYAW ZIN LATT ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The Schwaner Mountains area is located in the Southwest Kalimantan Islands, Indonesia. After the deposition of Permo-Carboniferous sediments on a basement complex of crystalline schists and the emplacement of gabbroic plutonic masses, the zone of the Schwaner Mountains had been invaded by large granitic to quartz-dioritic (tonalitic) batholiths. Iron ore mineralization is formed with these granitic intrusions within the Schwaner Mountains. The purpose of this research is to study of the style of each iron ore mineralization and their mineralogical and geochemical characteristics of different iron ore mineralizations associated with granitic intrusions as well as the geochemical characteristics of granitic rocks. During this research, four iron ore mineralizations are visited to study their nature, style, petrographic studies and significant geochemical characteristics of each iron ore. Ruwai iron ore mineralization is directly associated with dioritic intrusion and the iron ore mineralization occurs as the massive iron ore at the contact of intrusion and volcanic unit from the hanging wall. The iron ore mineralization style is characterized by skarn style mineralization and the principle ore minerals are magnetite and hematite that occur within the proximal garnet zone. The next iron ore mineralization Sejambuan iron ore occurs as a massive body at the contact zone between granite intrusion and volcanic andesite unit which is highly altered with kaolinite and illite mineral assemblages. The iron ore mineralization is associated with alteration envelopes and alterations are seemed to be products of hydrothermal event. The Ombangan iron ore mineralization is located near the Ruwai iron ore mineralization and the iron mineralization here occurs as massive magnetite associated with granite intrusions and volcanic-sedimentary units. The mineralization style is considered as skarn style mineralization associated with intrusion. The evidence of skarn mineral assemblages garnet occurs within the ore zone and those are replaced by magnetite. The last iron ore mineralization, the Bukit Besi iron ore mineralization, is different from the other three iron mineralizations in area. The principle iron ore minerals hematite occurs associated with the alternating band of microcrystalline quartz (chert). The geochemical signatures of each iron ore are entirely composed of Fe2O3 and slightly different variable concentration of other major element oxides. The encountered incompatible trace elements are generally low concentrations except the transition and chalcophile elements are variable for each iron deposit. The rare earth elements are generally depleted and most of their REE chondite-normalized patterns display fractionation LREE in respect to HREE and some are displayed with distinct positive Ce and Eu anomalies.